Analisis Laporan Keuangan Untuk Menilai Kinerja Keuangan Pemerintah Daerah Labuhan Batu - Purba, Sahala; Hutabarat2, Eloy Charolina; Simbolon, Romaito; Simarmata, Ary Dratma; Surbakti, Ekel Gia (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
This study aims to evaluate the financial performance of the Labuhan Batu district government based on financial report data from 2013 to 2022. In this study, the approach used is descriptive research with a background in phenomena such as unemployment rates and poverty rates in Labuhan Batu district from 2013 to 2022. The results of the analysis from 2013 to 2022 show that the financial performance of Labuhan Batu district is seen from: (1) the regional financial independence ratio is still very low because the average ratio is 22.57% with an instructive relationship pattern that illustrates that the level of community welfare is very low (2) The regional financial dependency ratio is relatively low because the average is 12.12%, so the level of dependence of the regional government on central and/or provincial government revenues is relatively low (3) The ratio of the degree of fiscal decentralization is relatively low with an average of 12.12% (4) The ratio of the effectiveness of regional original income is relatively less effective because the average effectiveness is still below 100%, namely 83.17% (5) The ratio of the efficiency of regional original income can It is said to be inefficient because the average is 83.17%, so the performance of the regional government can be said to be inefficient in Labuhan Batu district (6) The regional tax effectiveness ratio is classified as less effective because it has an average of 79.87% (7) The regional tax efficiency ratio is classified as very efficient in collecting regional taxes with an average of 3.79%, so the collection of regional taxes in Labuhan Batu is increasingly efficient (8) The BUMD contribution ratio is classified as contributing very low with average 9.04% Keywords: Financial Report Analysis, Financial Performance of the Labuhan Batu Regency Government